Alterations of the microenvironment of hepatocellular carcinoma in different unfolded protein response activity states - Yao Wang; Xiao Fei Zhu; Wan Jian Gu; Gui Hong Zhang (Discover Oncology)
Abstract Background The unfolded protein response (UPR) is an adaptive and cytoprotective sensing-signaling network. Numerous studies have indicated the crucial role of UPR in the anti-tumor drug resistance and the modification of tumor microenvironment (TME). The aim of this study is to analyze the alterations of microenvironment and key regulatory genes in hepatocellular carcinoma (HCC) with high UPR activity. Methods We profiled differentially expressed genes (DEGs) by UPR activity, and the biological functions of DEGs and the alterations of signaling pathways were explored. The Immune/Stromal scores and relative abundance of infiltrating cells of HCC tissues with RNA sequencing data downloaded from The Cancer Genome Atlas (TCGA) were calculated by the xCell and ESTIMATE algorithm. The correlations between the prognostic UPR-related genes with the microenvironment scores and infiltrating cells were analyzed using R package “corrplot”. Results Our results demonstrated that UPR-related genes mainly involved in immune-related signaling pathways. Microenvironment analysis revealed that HCC tissues with higher UPR activity had lower Stromal scores and the relative abundance of various infiltrating cells including hematopoietic stem cells (HSC), lymphatic endothelial cells (LECs), microvascular endothelial cells, endothelial cells (ECs) and adipocytes decreased most significantly. Kaplan–Meier survival analysis indicated that the decline of Stromal scores and corresponding infiltrating stromal cells would result in worse prognosis. The expression levels of CLEC3B, RAMP3, GPR182 and DNASE1L3 were significantly positively correlated with Stromal scores and various infiltrating stromal cells, and down-regulation of these genes were also associated with worse prognosis of HCC. Conclusions HCC with high UPR activity had lower Stromal scores and worse prognosis. Down-regulated genes CLEC3B, RAMP3, GPR182 and DNASE1L3 may play an important regulatory role in the modification of microenvironment of HCC with high UPR activity.